1996
DOI: 10.1021/jo9518314
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Direct Electrochemical Cross-Coupling between Aryl Halides and Activated Alkyl Halides

Abstract: The electrochemical reduction of a mixture of aryl halides and activated alkyl halides in DMF in the presence of catalytic amount of NiBr(2)bipy leads to cross-coupling products in good to high yields. The method applies to the synthesis of alpha-aryl ketones, alpha-aryl esters, and allylated compounds from readily available organic halides. Optimization of the process has been obtained by slowly adding the most reactive organic halide (usually the activated alkyl halide) during the electrolysis which is best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(88 citation statements)
references
References 63 publications
2
83
0
Order By: Relevance
“…While the direct coupling of haloarenes with haloalkanes by the action of stoichiometric sodium metal (Wurtz–Fittig reaction) predates conventional cross-coupling, 10 the development of more mild, transition-metal-catalyzed approaches has largely 11 been limited to the electrochemical coupling of activated alkyl halides such as α-halogenated carbonyls, 12 allylic acetates, 13 and benzyl halides. 14 A majority of the studies are electrochemical, and in many cases these methods required a substantial excess of one organic halide, 12a,12e,12f,13c,13e slow addition of one reactant, 14b or both.…”
Section: Introductionmentioning
confidence: 99%
“…While the direct coupling of haloarenes with haloalkanes by the action of stoichiometric sodium metal (Wurtz–Fittig reaction) predates conventional cross-coupling, 10 the development of more mild, transition-metal-catalyzed approaches has largely 11 been limited to the electrochemical coupling of activated alkyl halides such as α-halogenated carbonyls, 12 allylic acetates, 13 and benzyl halides. 14 A majority of the studies are electrochemical, and in many cases these methods required a substantial excess of one organic halide, 12a,12e,12f,13c,13e slow addition of one reactant, 14b or both.…”
Section: Introductionmentioning
confidence: 99%
“…42 Although Durandetti and Périchon had suggested it may play a role in XEC, there was no evidence to differentiate it from two sequential oxidative additions at a single nickel center. 43 This would result in a penultimate alkyl(aryl)Ni(IV)X 2 intermediate, followed by rapid reductive elimination of the cross-coupled product. 44 Our recent report 40 showed that the degree of rearrangement of 5-hexenyl iodide, a radical clock, depended on the concentration of nickel in the reaction mixture, consistent with a radical chain mechanism.…”
Section: Strategies For Achieving Useful Yields Of Cross-coupled Prodmentioning
confidence: 99%
“…Catalytic processes based on the use of electrogenerated nickel(0) bipyridine complexes have been a prominent theme in the laboratories of Nédélec, Périchon, and Troupel; some of the more recent work has involved the following: (1) cross-coupling of aryl halides with ethyl chloroacetate [143], with activated olefins [144], and with activated alkyl halides [145], (2) coupling of organic halides with carbon monoxide to form ketones [146], (3) coupling of α-chloroketones with aryl halides to give α-arylated ketones [147], and (4) formation of ketones via reduction of a mixture of a benzyl or alkyl halide with a metal carbonyl [148].…”
Section: Catalytic Reduction Of Carbon-halogen Bondsmentioning
confidence: 99%